GROWTH PERFORMANCE OF Clarias gariepinus JUVENILES FED PROCESSED ALMOND (Terminalia catappa LINNAEUS) KERNEL MEAL (2016)
Increasing cost of feedstuff due to competition between livestock and human necessitates research into Low-Cost Unconventional Feedstuffs (LCUF) for profitable fish farming. Almond kernel has been reported to be nutrient-rich feedstuff for livestock; however information on the potential of almond (Terminalia catappa) as a LCUF has not been well documented in aquaculture. Therefore, the use of almond kernel meal as a replacement for soybean meal in the diet of Clarias gariepinus was investigated.Chemical compositions of Soaked almond kernel meal (SOAM), Boiled almond kernel meal (BOAM), Roasted almond kernel meal (ROAM), Mechanically extracted almond kernel meal (MEAM), Solvent (petroleum spirit) extracted almond kernel meal (SEAM) and Raw almond kernel meal (RWAM) were determined using standard procedures. Crude protein digestibility of the meals was conducted using C. gariepinus juveniles (n = 420, 9.15±0.08 g). Two meals with highest crude protein digestibility were used for nutrient utilisation and growth studies. Each of these meals was used to replace soybean meal at 0.0, 25.0, 50.0, 75.0 and 100.0% in formulating isonitrogenous (40% crude protein) diets. The diets were fed to C. gariepinus (n = 600, 12.02±0.04 g) twice daily at 3.0% body weight for 105 days. Mean weight gain (MWG), Specific growth rate (SGR) and Feed conversion ratio (FCR) were calculated. Blood (5mL) was sampled from the fish for Packed Cell Volume (PCV), White Blood Cell (WBC), Plasma protein and albumin determination using standard procedures. Histopathological evaluations of the liver and kidney were carried out using standard procedures. Data were subjected to descriptive statistics and ANOVA at ά0.05.Crude protein values significantly varied from 24.1% in BOAM to 35.4% in SEAM. Crude fibre ranged from 3.3% (ROAM) to 3.8% (SEAM). Phosphorus (0.5%) and calcium (0.3%) were highest in ROAM, while lowest values of phosphorus (0.2%) and calcium (0.2%) were in RWAM. Phytate ranged from 0.04% (ROAM) to 0.09% (RWAM), while tannin ranged from 0.03% (ROAM) to 0.07% (RWAM). Fish fed ROAM had highest crude protein digestibility (89.0%) followed by MEAM (88.9%) while the least value (87.1%) was recorded in fish fed SEAM. High MWG (69.0±2.9g; 68.5±1.5g), SGR (1.82%; 1.81%) and least FCR (1.54±0.05; 1.53±0.03) were obtained in fish fed 75.0% ROAM and MEAM, respectively, while the lowest values of MWG (27.0±0.9g), SGR (1.12%) and highest FCR (2.1±0.2) were obtained in fish fed 100.0% ROAM. Elevated PCV (28.0%) was obtained in fish fed 50.0% MEAM inclusion, while least PCV (23.0%) was obtained in fish fed 100.0% ROAM. The WBC significantly varied from 10.3±0.05x106/μl to 11.8±0.01x106/μl in fish fed 0.0% MEAM and 100.0% ROAM, respectively. Fish fed 50.0% MEAM had significantly higher plasma protein (4.8±0.1g/dL) and albumin (2.9±0.1g/dL), while significantly lower levels of plasma protein (3.4±0.01g/dL) and albumin (1.8±0.1g/dL) were obtained at 100.0% ROAM. Vascular fibrosis of the liver and tubular necrosis of the kidney were observed in fish fed ROAM and MEAM at inclusion levels above 75.0%. Roasted almond kernel meal could replace soybean meal up to 75.0% in Clarias gariepinus diet. Growth depression and health impairment could result from replacement beyond this level